Revealing the extent of the first wave of the COVID-19 pandemic in Kenya based on serological and PCR-test data - Ojal, J; Brand, SP; Were, V; Okiro, EA; Kombe, IK; Mburu, C; Aziza, R; Ogero, M; Agweyu, A; Warimwe, GM; Uyoga, S; Adetifa, IMO; et al. (F1000 Research, 2021)
Policymakers in Africa need robust estimates of the current and future spread of SARS-CoV-2. We used national surveillance PCR test, serological survey and mobility data to develop and fit a county-specific transmission model for Kenya up to the end of September 2020, which encompasses the first wave of SARS-CoV-2 transmission in the country. We estimate that the first wave of the SARS-CoV-2 pandemic peaked before the end of July 2020 in the major urban counties, with 30-50% of residents infected. Our analysis suggests, first, that the reported low COVID-19 disease burden in Kenya cannot be explained solely by limited spread of the virus, and second, that a 30-50% attack rate was not sufficient to avoid a further wave of transmission.